Responsive Polymer-Electrode Interface—Study of its Thermo- and pH-Sensitivity and the Influence of Peptide Coupling. (1st March 2017) - Fandrich, A.; Buller, J.; Memczak, H.; Stöcklein, W.; Hinrichs, K.; Wischerhoff, E.; Schulz, B.; Laschewsky, A.; Lisdat, F.
Abstract: This study introduces a thermally responsive, polymer-based electrode system. The key component is a surface-attached, temperature-responsive poly(oligoethylene glycol) methacrylate (poly(OEGMA)) type polymer bearing photoreactive benzophenone and carboxy groups containing side chains. The responsive behavior of the polymer in aqueous media has been investigated by turbidimetry measurements. Polymer films are formed on gold substrates by means of the photoreactive 2-(dicyclohexylphosphino)benzophenone (DPBP) through photocrosslinking. The electrochemical behavior of the resulting polymer-substrate interface has been investigated in buffered [Fe(CN)6 ] 3- /[Fe(CN)6 ] 4- solutions at room temperature and under temperature variation by cyclic voltammetry (CV). The CV experiments show that with increasing temperature structural changes of the polymer layer occur, which alter the output of the electrochemical measurement. Repeated heating/cooling cycles analyzed by CV measurements and pH changes analyzed by quartz crystal microbalance with dissipation monitoring (QCM-D) reveal the reversible nature of the restructuring process. The immobilized films are further modified by covalent coupling of two small biomolecules - a hydrophobic peptide and a more hydrophilic one. These attached components influence the hydrophobicity of the layer in a different way - the resulting change of the temperature-caused behavior has been studied by CV indicating a different state of the polymer after coupling of the hydrophobic peptide.